Exploring genetic diversity and disease response of cultivated rice accessions (Oryza spp.) against Pyricularia oryzae under rainfed upland conditions in Benin - Yelome, O.I.; Audenaert, K.; Landschoot, S.; Dansi, A.; Vanhove, W.; Silué, D.; Damme, P.V.; Haesaert, G. (Springer, 2018)
The main goal of this study is to gain insight into the relationship between the genetic profile of cultivated rice (Oryza spp.) accessions and their resistance to rice blast. Therefore, the genetic and phenotypic variability of a set of 350 cultivated rice accessions originating from Africa (Benin, Mali and Nigeria, Ivory Coast etc.) was examined. Seventy-seven fluorescent amplified fragment polymorphism (AFLP) markers were used to gain insight into the genetic variation and to classify the germplasm collection. In addition, the rice germplasm was assessed for its resistance to blast disease caused by Pyricularia oryzae in upland field conditions. Huge differences in responses of rice accessions to P. oryzae were observed, ranging from highly susceptible to highly resistant. Twelve percent of all accessions were highly resistant to P. oryzae. Based on their AFLP marker profile these highly resistant accessions could be separated from the other accessions. Stepwise regression revealed that the best prediction of the blast resistance level was achieved with a maximum number of 13 AFLP markers. Marker CTA22 was the most important for accurate prediction of blast resistance, this marker was present in all highly resistant accessions. It can be concluded that AFLP markers are a valuable tool to screen rice accessions for their susceptibility towards blast disease and that, based on a subset of markers, it is possible to predict the resistance to rice blast.